2023
DOI: 10.1177/10998004231178318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi on Lung Function, Exercise Capacity and Psychosocial Outcomes in Patients With Chronic Obstructive Pulmonary Disease: Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Objectives: To explore whether tai chi can improve lung function, exercise capacity, and health-related outcomes in patients with chronic obstructive pulmonary disease (COPD). Methods: The PubMed, Embase, Cochrane Central Register of Controlled Trials, Chinese National Knowledge Infrastructure (CNKI), Wanfang, and China Science and Technology Journal Database (VIP) databases were searched from inception to January 5, 2023. The methodological quality of the included studies was evaluated according to the Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Tai Ji and Qigong (Yijinjing, Liuzijue, Baduanjin et al) are traditional Chinese mediative movements, originated from thousand years ago, combine with sustained mindfulness, deep diaphragmatic breathing, and gentle movements, applied as the complementary medicine in treating chronic disease, could improve patient's cardiac and lung function, release chronic fatigue or pain, finally benefit patient's physical and mental health. Several systematic reviews (SRs) previously revealed that Tai Ji and Qigong are traditional PR, and could improve FEV1, 6WMD, and QoL for patients with COPD [6,7] . The positive conclusion was seemed certain, however most RCTs included in research were published in Chinese and complained as low quality due to high risk of either randomization or allocation concealment bias.…”
Section: Introductionmentioning
confidence: 99%
“…Tai Ji and Qigong (Yijinjing, Liuzijue, Baduanjin et al) are traditional Chinese mediative movements, originated from thousand years ago, combine with sustained mindfulness, deep diaphragmatic breathing, and gentle movements, applied as the complementary medicine in treating chronic disease, could improve patient's cardiac and lung function, release chronic fatigue or pain, finally benefit patient's physical and mental health. Several systematic reviews (SRs) previously revealed that Tai Ji and Qigong are traditional PR, and could improve FEV1, 6WMD, and QoL for patients with COPD [6,7] . The positive conclusion was seemed certain, however most RCTs included in research were published in Chinese and complained as low quality due to high risk of either randomization or allocation concealment bias.…”
Section: Introductionmentioning
confidence: 99%